Suppression of neutrophils by sodium exacerbates oxidative stress and arthritis - Zlatar, Leticija; Mahajan, Aparna; Munoz Becerra, Marco; Weidner, Daniela; Bila, Galyna; Bilyy, Rostyslav; Titze, Jens; Hoffmann, Markus H.; Schett, Georg; Herrmann, Martin; Steffen, Ulrike; Muñoz, Luis E.; et al. (Frontiers in Immunology, 2023)
Introduction: Typical Western diet, rich in salt, contributes to autoimmune disease development. However, conflicting reports exist about the effect of salt on neutrophil effector functions, also in the context of arthritis. Methods: We investigated the effect of sodium chloride (NaCl) on neutrophil viability and functions in vitro, and in vivo employing the murine K/BxN-serum transfer arthritis (STA) model. Results and discussion: The effects of NaCl and external reactive oxygen species (H2O2) were further examined on osteoclasts in vitro. Hypertonic sodium-rich media caused primary/secondary cell necrosis, altered the nuclear morphology, inhibited phagocytosis, degranulation, myeloperoxidase (MPO) peroxidation activity and neutrophil extracellular trap (NET) formation, while increasing total ROS production, mitochondrial ROS production, and neutrophil elastase (NE) activity. High salt diet (HSD) aggravated arthritis by increasing inflammation, bone erosion, and osteoclast differentiation, accompanied by increased NE expression and activity. Osteoclast differentiation was decreased with 25 mM NaCl or 100 nM H2O2 addition to isotonic media. In contrast to NaCl, external H2O2 had pro-resorptive effects in vitro. We postulate that in arthritis under HSD, increased bone erosion can be attributed to an enhanced oxidative milieu maintained by infiltrating neutrophils, rather than a direct effect of NaCl.
CRIS-Team Scopus Importer:2023-09-01
Keywords: K/BxN serum transfer arthritis; neutrophil extracellular traps (NETs); neutrophils; osteoclasts; reactive oxygen species; sodium chloride